Dissecting genetic links between Alzheimer’s disease and type 2 diabetes mellitus in a systems biology way - Kang, Peiyuan; Wang, Zhao; Qiao, Dan; Zhang, Bohan; Mu, Chenyu; Cui, Huixian; Li, Sha (Frontiers in Genetics, 2022)
Background: Alzheimer's disease (AD) and Type 2 Diabetes Mellitus (T2DM) are two of the most common diseases for older adults. Accumulating epidemiological studies suggest that T2DM is a risk factor for cognitive dysfunction in the elderly. In this study, we aimed to dissect the genetic links between the two diseases and identify potential genes contributing the most to the mechanistic link. Methods: Two AD (GSE159699 and GSE28146) and two T2DM (GSE38642 and GSE164416) datasets were used to identify the differentially expressed genes (DEGs). The datasets for each disease were detected using two platforms, microarray and RNA-seq. Functional similarity was calculated and evaluated between AD and T2DM DEGs considering semantic similarity, protein-protein interaction, and biological pathways. Results: We observed that the overlapped DEGs between the two diseases are not in a high proportion, but the functional similarity between them is significantly high when considering Gene Ontology (GO) semantic similarity and protein-protein interactions (PPIs), indicating that T2DM shares some common pathways with AD development. Moreover, we constructed a PPI network consisting of AD and T2DM DEGs, and found that the hub gene SLC2A2 (coding transmembrane carrier protein GLUT2), which connects the most DEGs in both AD and T2DM, plays as a key regulator in linking T2DM and AD via glucose metabolism related pathways. Conclusions: Through functional evaluation at the systems biology level, we demonstrated that AD and T2DM are similar diseases sharing common pathways and pathogenic genes. SLC2A2 may serve as a potential marker for early warning and monitoring of AD for the T2DM patients.